Evaluación del efecto de la cianocobalamina sobre el desarrollo de ovocitos recuperados de ovarios bovinos post mortem de centros de faenamiento, en el laboratorio de biotecnología de la reproducción de la carrera de medicina veterinaria de la universidad técnica de Cotopaxi. - Andrade Males, Vannessa Belén (2020)
This project is based on the application of assisted reproduction techniques in order to contribute and favor the substantial improvement of livestock production by the technique of ovum pick up (OPU) consisting of collecting ovaries post mortem use of oocytes in order to exploit biological resources and use them in the study of oocyte development with the addition of cyanocobalamin. This study aims at evaluating the effect of cyanocobalamin on the development of oocytes postmortem in order to test the efficiency of it in the middle of maintenance and evaluation of oocytes. The project was conducted in the laboratory of Veterinary Medicine at the Technical University of Cotopaxi was developed by collecting 60 ovaries of cows post mortem of two centers of slaughter, the ovaries were collected after slaughter of the animal by cutting with scissors and then They are the placed in a sheath ziplop containing 400ml of sodium chloride at 9% tempered at 38.5 ° C. Ovaries were transported at a temperature of 38.5 in an isothermal heat until arrival at the laboratory, we proceeded to perform the technique for follicular aspiration and recovery of oocytes to being categorized and evaluated were divided into two groups being the group T0 control and treatment group were evaluated both T1 to the passage 12 and 24 hours to obtain the results of the project, where it can be said that the addition of cyanocobalamin does not generate a relevant impact on the means of evaluation and maintenance of oocytes.